Use of hydrogen-rich solvent and principal component analysis improves the recovery of phytochemicals from grape wastes - Tunahan Engin; Ayhan Çiğdem; Enes Kavrut; Betül Tan; Duried Alwazeer; Kairat Bekbayev; Akerke Toleugazykyzy; Bakytzhan Bolkenov; Roza Bekbayeva; Kamila Baichiyeva (Journal of Agriculture and Food Research)
Grape wastes (peels, seeds, and stems) are wine and fruit juice wastes rich in phytochemicals. This study aimed to evaluate the efficiency of hydrogen-rich solvents (HRS), including hydrogen-water (HRW), hydrogen-rich ethanol (HRE), and hydrogen-rich methanol (HRM) to recover flavonoids, phenolics, and antioxidants of grape wastes. All phytochemicals (phenolics, flavonoids, and antioxidants) were better recovered by HRSs. Methanol and HRM generally better-recovered phytochemicals than other pure and hydrogen-rich solvents, respectively. Principal component analysis (PCA) plots were used to evaluate the discrimination between the samples. PCA showed that phytochemical content and type vary according to the type of grape waste. While the HRW, methanol, and HRM results of the grape seed samples were on the right side of PCA 1, the results of water, ethanol, and HRE were on the left side of PCA 1. Similarly, the water, HRW, methanol, and HRM results of the grape stem samples were on the right side of PCA 1, while the results of ethanol and HRE were on the left side of PCA 1. However, the results of the grape stem samples' ethanol, methanol, HRE, and HRM were on the right side of PCA 1, while pure water and HRW were on the left side of PCA 1. HPLC results showed that the phenolic compounds in grape seeds were higher than in the skins and stems. HRSs increased the recovery of some phenolic compounds like catechin and chlorogenic acid and preserved others. HRS is one of the sustainable and cost-effective techniques used in phytochemical extraction. This direction will give the industry a new perspective on recovering phytochemicals from grape and other agri-food wastes and preparing value-added products using a sustainable technique.